Penerapan Media Gambar sebagai Upaya Meningkatkan Kemampuan Pemahaman Matematika Siswa Kelas IV SDN 016 Kopah pada Materi Pembagian - Elsya Meizahwa (Universitas Muhammadiyah Enrekang, 2023)
learning media in the form of images is a tool that can be used by an educator in a learning process with the aim of creating meaningful learning for student. This reaserch aims to determine the effect of using image media on students at SDN 016 Kopah. The type of research subjects were class IV teachers and 30 student. The data collection methods used were observation and interviews. The results of the research show that the teacher’s strategy of using image media in the distribution materials for class IV stdent at SDN 016 Kopah is that students it is easy for students to devide because the picturescgiven are related to student’s daily lives.